Theory of Valuation: Frontiers of Modern Financial Theory - Duffie, Darrell (Review of Financial Studies, 1989)
If you pick up a copy of Theory of Valuation,1 and I suggest that you do, the first thing likely to impress you is the length of the editors' last names (26 letters in total). After getting over that, you will probably turn to the table of contents to see which of your friends or mentors are represented. If you are like me, you might be embarrassed that you had not yet read one (I will not say which one in my case), or perhaps more, of these classics, and you might feel that there are one or more pieces that might have been added. Perhaps your choices would include Harrison and Kreps' (1979) martingale characterization of security prices or Arrow's (1953) paper on “The Role of Securities in the Optimal Allocation of Risk Bearing,” (still required reading for doctoral finance students at Stanford). On the whole, however, you will be impressed. If you teach a course on asset pricing theory for doctoral students, you are likely to adopt this book as a supplementary text. If you read the book from cover to cover, including the mainly excellent new discussions, you will have fun and will profit from the time spent.